Walsburg, Riley County - Adcock, Tamar (Kansas State University, The Chapman Center for Rural Studies, 2012)
Swedish settlers founded Walsburg in 1866, naming it after nearby Walnut Creek. A small Swedish community grew there for decades. However, after the Union Pacific Railroad left town in 1935, Walsburg declined and became a lost community.
Tamar Adcock, “Walsburg, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/147.
Keywords: Church; Riley County; Swedes; Union Pacific Railroad; Walsburg; Kansas